Adaptability and Quality Practices for Customer-Centered Retail: Strengthening Nanostores in Vulnerable Communities - Ortega-Jimenez, Cesar H; Sabillon Palomeque, Dany N.; Melgar-Martínez, Narciso A; Tomé, José (LACCEI, 2025)
This study explores how adaptability, framed by Total Quality Management (TQM) principles, influences customer experience in nanostores. Using data from 143 nanostore owners, managers, and employees in Honduras, the study finds that adaptability significantly drives TQM practices (path coefficient = 0.68, p < 0.001), which, in turn, improve customer experience (path coefficient = 0.72, p < 0.001). Adaptability also directly influences customer satisfaction (path coefficient = 0.45, p < 0.001), highlighting the importance of market agility. Aligned with the principles of humanitarian engineering for sustainable development in Latin America, this research underscores the need for context-sensitive strategies that integrate adaptability and total quality management to foster innovation, build resilience, and enhance long-term competitiveness in small-scale retail environments. The study suggests that prioritizing adaptability and embedding TQM principles enhances service quality and customer loyalty. Future research should investigate the long-term impact of digitalization on nanostores’ adaptability and customer experience, particularly in response to evolving consumption patterns and technologies. Ongoing data collection in Honduras, Colombia, and Peru will explore scalable paths to innovation and sustainable development for micro-retail ecosystems in Latin America.